Late Simultaneous Metastasis of Renal Cell Carcinoma to the Submandibular and Thyroid Glands Seven Years after Radical Nephrectomy - Miah, Mohammed S. (Hindawi Publishing Corporation, 2010)
Background. Renal cell carcinoma (RCC) metastasis to the salivary glands is extremely rare. Most cases reported previously have involved the parotid gland and only six cases involving the submandibular gland exist in the current literature. Metastasis of RCC to thyroid gland is also rare but appears to be more common than to salivary glands. Methods and Results. We present the first case of simultaneous metastasis to the submandibular and thyroid glands from clear cell RCC in a 61-year-old woman who presented seven years after the primary treatment. The submandibular and thyroid glands were excised completely with preservation of the marginal mandibular and recurrent laryngeal nerves, respectively. Conclusion. Metastatic disease should always be considered in the differential diagnosis for patients who present with painless salivary or thyroid gland swelling with a previous history of RCC. If metastatic disease is confined only to these glands, prompt surgical excision can be curative.